Effect of intravenous urokinase vs best medicine treatment on functional outcome for patients with acute minor stroke (TRUST): a randomized controlled trial - Yongli Tao; Yuan Gao; Lu Zhao; Yafang Xu; Chenyang Jiang; Kai Liu; Hui Fang; Lulu Pei; Xin Wang; Rui Zhang; Jun Wu; Jing Yang; et al. (BMC Medicine, 2025)
Abstract Background The benefits of intravenous thrombolysis in patients with acute minor stroke remain controversial. For the aim of providing a better therapeutic strategy, high-quality trials are required to validate the efficacy of thrombolytic medicine other than intravenous recombinant tissue plasminogen and tenecteplase. In the trial, we evaluate the efficacy and safety of urokinase (UK) in acute minor stroke. Methods This multicenter, open-label, blinded-endpoint, randomized controlled clinical trial enrolled patients with minor stroke within 6 h of symptom onset, with a NIHSS score ≤ 5. The trial was conducted at 25 hospitals in China between October 2020 and February 2023. Eligible patients were randomized to the UK group (1,000,000 U) or the best medicine treatment group. The responsible investigator recommended and implemented the best medicine treatment based on guidelines. The primary endpoint was an excellent functional outcome, defined as a modified Rankin scale (mRS) score of 0–1 at 90 days. The primary safety outcome was symptomatic intracranial hemorrhage (sICH) within 36 h. Results A total of 999 patients were enrolled in the trial, the median age was 64 years, 371 (36.9%) were women; the median (IQR) NIHSS score was 3 (2–4). At 90 days, the primary endpoint was observed in 427 patients (84.9%) in the UK group and 425 patients (85.7%) in the control group (adjusted risk ratio [RR] 1.00, 95% CI 0.96–1.05, p = 0.87). A total of 3 patients in the UK-treated (0.6%) group experienced sICH compared to 1 patient (0.2%) in the control group (RR 1.83, 95% CI 0.16–20.27, p = 0.62). Conclusions For patients with acute minor stroke treated within 6 h of symptom onset, UK intravenous thrombolysis treatment was not found to be beneficial in terms of excellent functional outcome at 90 days, whereas it was safe. Trial registration ClinicalTrials.gov Identifier: NCT04420351.